The role of prophylactic prostatectomy as a primary prevention strategy in high-risk germline mutation carriers. Issue 5 (18th September 2022) - Tiwari, Raj; Clark, Roderick; Fleshner, Neil
Abstract : Purpose of review: Men with high-risk germline mutations are at significantly higher risk of developing and dying from prostate cancer. Current screening and treatment paradigms may lead to missed opportunities for cure. Herein we review the current literature on prevention, screening and treatment of these carriers and explore the potential role of prophylactic prostatectomy in primary prevention of prostate cancer mortality. Recent findings: Prostate-specific antigen (PSA)-based screening has demonstrated marginal benefits in prostate cancer (PCa) survival and uncertainty remains on its true benefit among high-risk carriers. Recent results indicate that PCa in BRCA 2 carriers occurs at a higher incidence, younger age and progresses more rapidly compared with noncarriers. An intensified screening protocol of MRI and PSA in young carriers demonstrated how using PSA values alone may be insufficient. Current evidence indicates that high-risk carriers have worse survival outcomes after undergoing radical treatment for screening detected disease when compared with noncarriers. Summary: Prophylactic prostatectomy within the context of a clinical trial is a reasonable primary prevention option for discussion with high-risk carriers, especially BRCA2 carriers during the shared decision-making process. Limitations exist in the current strategies of early PSA screening followed by radical treatment in this group.